Mashed up : music, technology, and the rise of configurable culture - Sinnreich, Aram (Science/technology/culture., 2010)
"From Ancient Times to the Present Day, writers have remarked on the unique power of music to evoke emotions, signal identity, and bond or divide entire societies, all without the benefit of literal representation. According to Aram Sinnreich, this power helps to explain why music has so often been regulated in societies around the globe--and why those regulations have been consistently resisted." "Mashed Up chronicles the rise of "configurability," an emerging musical and cultural moment rooted in today's global, networked communications infrastructure. Based on interviews with dozens of prominent DJs, attorneys, and music industry executives, the book argues that today's battles over sampling, file sharing, and the marketability of new styles such as "mash-ups" and "techno" presage social change on a far broader scale." "Àram Sinnreich is a sage guide to the emerging, perplexing, and downright vital world of configurable culture. He brings together a potent combination of deep academic learning, leading industry analyst credentials, and performing artist street cred. No one knows better than Sinnreich how music and technology are co-evolving."--Michael Heller, author of The Gridlock Economy: How Too Much Ownership Wrecks Markets, Stops Innovation, and Costs Lives." ""The greatest strength of this book is the broad, interdisciplinary range of its appeal: audiences interested in musicology, digital rights, street culture, and many other subjects will find it interesting, and it is written in a style that members of the general public would also appreciate. It is a book that could be assigned to undergraduates who are music majors and for courses in which intellectual property is a theme."--Elizabeth Losh, author of Virtualpolitik: An Electronic History of Government Media-Making in a Time of War, Scandal, Disaster, Miscommunication, and Mistakes." ""Young people who make new music by sampling existing work, who màsh up' existing cultural materials to convey entirely new messages, have been portrayed as thieves and copyright violators. Yet, as Aram Sinnreich eloquently teaches, what they are actually doing is pioneering new forms of cultural creation."--Howard Rheingold, author of Virtual Community: Homesteading on the Electronic Frontier." ""Mashed Up is an intellectual/emotional romp, filled with insights into the pleasures and paradoxes of our high-tech musical universe. Aram Sinnreich is an original thinker, a brilliant brother, and a bad mammajamma."--David Ritz, author of Divided Soul: The Life of Marvin Gaye."--Jacket